Labor Relations, Labor Relations Law and Public Policy - Montague, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1964)
In this address the author explains how and why, legislation in Canada appears to have compartmentalized its own activities within the labour market so that a number of legislative efforts are continued through the economy with little relationship one to the other.** This paper tvas presented at the First Meeting of the Canadian IndustrialRelations Research Institute, held at McGill University, July 6th, 1964.